2019
DOI: 10.1111/ctr.13712
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile colonization and infection in patients admitted for a first autologous transplantation: Incidence, risk factors, and patient outcomes

Abstract: Background More data are needed regarding the incidence, risk factors, and outcomes for Clostridioides difficile infection (CDI) and colonization in patients undergoing an autologous hematopoietic stem cell transplantation (AHSCT). Methods We studied 472 consecutive patients admitted for a first AHSCT and conducted a prospective C difficile stool surveillance and ribotyping analysis in a subset of 94 patients. Results Clostridioides difficile infection was diagnosed in 7% of patients for an incidence of 3.4 CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Another controversial point is the link between GVHD and CDI. In our analysis, the frequency of CDI was similar in patients with or without acute GVHD, as reported by other authors [15,19]. However, other studies [6,9,16] observed that CD was a significant risk factor for acute GVHD development, in particular for the cases involving the gastro-intestinal system, suggesting that gut dysbiosis and disruption of mucosal barriers might promote CDI as well as GVHD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another controversial point is the link between GVHD and CDI. In our analysis, the frequency of CDI was similar in patients with or without acute GVHD, as reported by other authors [15,19]. However, other studies [6,9,16] observed that CD was a significant risk factor for acute GVHD development, in particular for the cases involving the gastro-intestinal system, suggesting that gut dysbiosis and disruption of mucosal barriers might promote CDI as well as GVHD.…”
Section: Discussionsupporting
confidence: 90%
“…In our study the main risk factors for CDI development were antibiotic therapy before HSCT, previous abdominal surgery, HCV infection, and other bacterial and fungal infections identified before or concomitantly with CDI during hospitalization for HSCT. Therefore, the use of antibiotics before and during HSCT hospitalization remains the leading risk factor in our analysis as well as in previous studies [6,7,15]. Broad spectrum antibiotics, such as cephalosporines, penicillines and fluoroquinolones, are associated with gut dysbiosis, development of bacterial resistance, malabsorption and alteration of the gut-liver axis [3].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…40 In allo-HCT recipients with CDI, the LOS is longer leading to higher hospital costs. 41 In this study, the median LOS was 6 days longer for allo-HCT with CDI compared to controls, and 9.5 days longer for SOT with CDI compared to controls. We observed frequent fever (35% of allo-HCT with CDI) like other reports, 42 which was less frequent after SOT with CDI.…”
Section: Discussionmentioning
confidence: 52%